(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2025)
Question: How does the moss Atrichum undulatum affect changes in the NH4 + and NO3 – content in the soil under different ecological conditions of the Ukrainian Roztochchya forest ecosystems? Location: Ukrainian Roztochchya. Methods: field research in established plots with different ecological indicators. Nomenclature: Virchenko & Nyporko 2022. Results: The differences in the N mineral forms content under the moss Atrichum undulatum depending on its growth location in forest ecosystems were established. It was found that in summer, in areas of old-growth forest under more favorable soil microconditions, the amount of NH4 + and NO3 – under moss was higher compared to areas of felling and recreation, which is probably caused by more active fixation and exchange of N with the participation of microbiota and by leaching of mineral compounds from the brown part of turf. It was established that in all areas of forest ecosystems, the NH4 + content under moss was higher than in soil without turfs. However, the amount of the NO3 – under turf in the reserve area (19,5±0,6 mg/kg d. s.) and in the recreation area (17,1±0,5 mg/kg d. s.) was lower than that without plants (20,3±0,7 mg/kg d. s. and 18,7±0,8 mg/kg d. s., respectively), which probably indicates its more active absorption by the gametophyte under higher moisture supply of soil than in the felling. It was determined that in xeromorphic conditions of felling, extreme indicators of insolation and water-thermal regime of the soil surface layer caused a significant decrease in the NH4 + and NO3 – content in the substrate without turfs. Under the turf in the felling zone, the temperature was lower and the humidity was higher, which contributed to the functional activity of microbiota and increasing in the amount of N mineral compounds. The pH value under moss was more acidic compared to soil without turfs, and probably created optimal conditions for N fixation and mineralization, which led to greater amount of, particularly NH4 +. Apparently, the effect of ecological factors on the NH4 + and NO3 – content had comprehensive character: both the pH value and the hydro-thermal regime of the microenvironment were affected. Conclusion. In various ecological conditions of the reserve and disturbed of forest ecosystems moss cover changing the hydrothermal and chemical characteristics of the soil promotes the activation of redox reactions associated with N transformation (increasing of the NH4 + and NO3 – content) with participation of soil microbiota.